Approved Anti-Obesity Medications in 2022 KSSO Guidelines and the Promise of Phase 3 Clinical Trials: Anti-Obesity Drugs in the Sky and on the Horizon - Eonju Jeon; Ki Young Lee; Kyoung-Kon Kim (Journal of Obesity & Metabolic Syndrome, 2023)
Obesity is a prevalent global health issue affecting approximately half of the world’s population. Extensive scientific research highlights the urgent need for effective obesity management to mitigate health risks and prevent complications. While bariatric surgery has proven to be highly effective, providing substantial short-term and long-term weight loss and resolution of obesity-related comorbidities, it is important to recognize its limitations and associated risks. Given the global obesity epidemic and the limitations of surgical interventions, there is high demand for effective and safe anti-obesity medications (AOMs). In Korea, the Korean Society for the Study of Obesity strongly advocates for the use of pharmacotherapy in Korean adults with a body mass index of 25 kg/m2 or higher who have not achieved weight reduction through non-pharmacological treatments. Currently, five AOMs have been approved for long-term weight management: orlistat, naltrexone/bupropion, phentermine/topiramate, liraglutide, and semaglutide. Tirzepatide is awaiting approval, and combination of semaglutide/cagrilintide and oral semaglutide are currently undergoing rigorous evaluation in phase 3 clinical trials. Furthermore, other promising drugs, including orforglipron, BI 456906, and retartrutide, are progressing to phase 3 studies, expanding the therapeutic options for obesity management. In personalized patient care, physicians play a crucial role in accurately identifying individuals who genuinely require pharmacotherapy and selecting appropriate AOMs based on individual patient characteristics. By integrating evidence-based interventions and considering the unique needs of patients, healthcare professionals significantly contribute to the success of obesity management strategies.